Pengaruh Kombinasi Serat Aren dan Pasir terhadap Pertumbuhan Pakchoi (Brassica rapaL. ssp.Chinensis) pada Hidroponik Substrat - Dewi, Reni Surya; Samanhudi, Samanhudi; Hardjoko, Dwi (Universitas Sebelas Maret, 2014)
Changed over of the functions of agricultural land into industrial areas causing the narrowness of potential agricultural land can be used for cultivation. Hydroponics is able to overcome these problems, one of them by utilizing arenga wood fiber as a substrate for planting. One type of vegetable which is easily cultivated mustard plants are especially pakchoi (Brassica rapa L. ssp. chinensis). In addition to the timing of harvest is short, the plant also has a high economic value. The purpose of this research is to know the composition of the mixture of arenga wood fiber for proper growth of the pakchoi. This research was carried out in July to September 2013 in Screen house B Sebelas Maret University Surakarta Faculty of agriculture. Research compiled based on Completely Randomized Design (CRD) with two factor, each consisting of three degrees so obtained nine ranks and one control which use husk charcoal and the treatment is replication four times. The Data obtained were analyzed with F-test standard of 5%. If there is a real significant on the treatment of variables measured then continued with average comparison test using Duncan Multiple Range Test (DMRT) at the 95% confidence level. The research shows that the arenga wood fiber can be used as a medium in hydroponic substrates for pakchoi and combinations are optimal for the growth of pakchoi is arenga wood fiber soaked water 6 days mix sand volcano not washed.